Afterword. Laser-light and interactions with particles (LIP), 2018. (March 2019) - Gouesbet, Gérard; Yang, Ping; Onofri, Fabrice
Abstract: Previous JQSRT special issues devoted to the "Laser-light and Interactions with Particles (LIP)" conferences were accompanied by prefaces written for issues published in a single volume, followed by peer-reviewer papers based on the topics discussed during the conferences, see Gouesbet and Brunel (2013)[1] in[2], Gouesbet and Onofri (2015)[3] in[4], and Gouesbet and Onofri (2017)[5] in[6] . Papers associated to the last LIP-conference, however, have been published as a virtual topical issue, the word "virtual" meaning that the papers have been published once they have been accepted, rather than collected in a single issue of JQSRT. In other words, the authors of accepted manuscripts have seen their papers officially published without having to wait for the rest of the manuscripts to get accepted. The present text is therefore rather an afterword than a preface.